Design, Synthesis and Biological Evaluation of Novel Piperazinone Derivatives as Cytotoxic Agents - Saeed Ghasemi; Simin Sharifi; Javid Shahbazi Mojarrad (Tabriz University of Medical Sciences, 2020)
Purpose: In this study, a series of piperazin-2-one derivatives were prepared through bioisosteric substitution of the imidazole ring of L-778,123 (imidazole-containing FTase inhibitor) and rearrangement of groups based on the tipifarnib structure. Final compounds were evaluated for their cytotoxic activities on cancer and normal cell lines by MTT assay. Methods: Methyl α-bromophenylacetic acid and 1-(3-chlorophenyl) piperazin-2-one were synthesized using previously described methods. Methyl 2-(4-chlorophenyl)-2-(4-(3- chlorophenyl)-3-oxopiperazin-1-yl) acetate was prepared by reaction between these two compounds in presence of potassium carbonate. Finally, methoxy group of ester was substituted by various amines such as guanidine, thiourea, urea and hydrazide. The synthesized compounds were tested for their cytotoxicity against colon cancer (HT-29) and lung cancer (A549) cell lines as well as MRC-5 (normal fetal lung fibroblasts) cells as a healthy cell line using MTT colorimetric assay method. Results: Replacement of imidazole moiety with guanidine, thiourea, and hydrazide could increase cytotoxicity toward all three cell lines. Some substituents, such as amine, urea, and hydroxylamine exhibited significant cytotoxicity (<500 µM) but lower than L-778,123 as standard compound. Hydroxyl and methoxy substituents did not show significant cytotoxicity. Imidazole substituent group revealed cytotoxicity similar to L-778,123 All compounds showed lower cytotoxic activity against normal cell lines compared with cancer cell lines. Conclusion: It seems the electron density of substituted groups and rearrangement of groups may significantly increase cytotoxic activity